Vpliv vlažnosti na dielektrične lastnosti lesa - Jošt, Matej (Les (Ljubljana), 2005)
In this article, the effect of moisture content on the dielectric properties of beech (Fagus sylvatica L.) and spruce (Picea abies L.) is presented. Dielectric properties of wood disks were measured at different moisture content. Measurements were performed at nine various frequencies of electromagnetic field(2, 3, ..., 10 MHz) and at room temperature, with impedance analyser HP 4191 A RF, using method by a micrometer screw with circular parallel electrodes. It was found out that dielectric constant of wood increases by increasing the moisture content of wood and decreases with increasing of frequency.
Keywords: les; vlažnost; Humidity; dielektrične lastnosti